DESIGN OF THE PUBLIC TRANSPORT TRAFFIC CONTROL WEB SYSTEM - POSTRELKO, YEVHENII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This article presents a comprehensive approach to the design and implementation of a web-based monitoring system specifically developed for managing and enhancing public transportation services within Kyiv. The system is designed to automate and streamline data collection from GPS-equipped public transport vehicles, allowing for continuous monitoring of key movement aspects, including route adherence, delays, unscheduled stops, and overall performance. One of the primary objectives is to support transportation departments in increasing operational efficiency by facilitating data-driven decision-making and enabling rapid responses to schedule disruptions and incidents on the road. A significant focus of the proposed solution is its intuitive user interface, which provides transport operators with access to critical data through interactive dashboards. These dashboards, powered by the Metabase business intelligence (BI) platform, allow users to dynamically visualize transport movement and track real-time data, including vehicle locations, delay patterns, and operational metrics. Metabase’s flexibility enables users to customize dashboards for specific routes, stops, or time intervals, enhancing analytical insights and supporting a range of operational and strategic needs. By integrating Metabase, the web system provides structured, visually digestible information, improving transparency and enabling coordinated actions across different transport departments. The proposed web system offers substantial potential for optimizing public transportation in Kyiv. Through continuous monitoring of delays, route deviations, and schedule adherence, it can help reduce passenger wait times, increase service reliability, and improve overall service quality. Additionally, the system’s data-driven approach supports long-term planning and scheduling optimizations, identifying recurring operational issues and enhancing transport authorities' ability to achieve a modernized, efficient, and user-centric public transit system that meets the demands of an evolving urban landscape.
Keywords: web system; public transport monitoring; dashboards; traffic control; transportation analytics; GPS; business intelligence